The good principal: A case study of early-career charter principals' role conceptualizations. (October 2019) - Truong, Felicia R.
Up to 75 percent of charter principals in the United States leave the role within five years. Understanding how early-career principals conceptualize the role could help strengthen principal preparation and in-service training. This study analyzed early-career charter principals' descriptions of the principalship in order to understand their framework for what it means to be a good principal. A qualitative case study was used, focused on semi-structured interviews with 15 charter school principals. Charter school principals in this study primarily defined being a 'good' principal using examples and descriptions of soft skills and personality traits.